2019
DOI: 10.3390/antibiotics8040266
|View full text |Cite
|
Sign up to set email alerts
|

The Inc FII Plasmid and its Contribution in the Transmission of blaNDM-1 and blaKPC-2 in Klebsiella pneumoniae in Egypt

Abstract: The emergence of bla KPC-2 and bla NDM-1 producing Klebsiella pneumoniae represents a great problem in many Egyptian hospitals. One hundred and twenty-six K. pneumoniae isolates from patients admitted to Assiut University Hospital were identified by an API20E kit. Carbapenemase-producing K. pneumoniae (CPKP) was detected by the modified carbapenem inactivation method (mCIM), the EDTA-modified carbapenem inactivation method (eCIM), and an E-test. Based on the polymerase chain reaction, all isolates were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…28 CRE Figure 8 Summary of the prevalence (%) of carbapenemase and ESBL genes in K. pneumoniae. Notes: Data from references 40,[55][56][57][58][59][60][61][62]70,80,[94][95][96][97][98][99] . a % of carbapenemase-resistant/-producing K. pneumoniae; b % of MDR K. pneumoniae; c % of ESBL-producing/third-generation cephalosporin-resistant K. pneumoniae; d % of ertapenem non-susceptible K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…28 CRE Figure 8 Summary of the prevalence (%) of carbapenemase and ESBL genes in K. pneumoniae. Notes: Data from references 40,[55][56][57][58][59][60][61][62]70,80,[94][95][96][97][98][99] . a % of carbapenemase-resistant/-producing K. pneumoniae; b % of MDR K. pneumoniae; c % of ESBL-producing/third-generation cephalosporin-resistant K. pneumoniae; d % of ertapenem non-susceptible K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Sukmawinata et al [10] demonstrated that the IncI1 plasmid was associated with the transmission of the gene bla CTX-M-2 in extended spectrum β-lactamase-producing E. coli, in thoroughbred racehorses in Japan. The study of Mohamed et al [11] reported that conjugative Inc FII plasmids had an important role in the spread of carbapenemase-producing Klebsiella pneumoniae in Egypt. Conjugative plasmids play an important role in the spread of antibiotic resistance, and their recognition is essential to limit their diffusion.…”
mentioning
confidence: 99%
“…Ramadan Mohamed et al reported that IncFIIK and FII plasmids play an important role in the dissemination of bla NDM-1 and bla KPC-2 among clinical strains of K. pneumoniae [1]. In our previous study, ST268 was reported in different hospitals in Kerman, Iran, as a new NDM-positive clone [17].…”
Section: Discussionmentioning
confidence: 95%
“…Risk factors that might increase nosocomial infections by K. pneumoniae include diabetes, long-term hospitalization, chronic obstructive pulmonary disease (COPD), transplantation, dialysis, neutropenia, excessive alcohol consumption and general weakness [1, 2]. The increase of carbapenem-resistant strains and the spread of plasmids carrying carbapenemase genes in K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation